Gold‐forming potential of the granitic plutons in the Xiaoqinling gold province, southern margin of the North China Craton: Perspectives from zircon U–Pb isotopes and geochemistry. (27th August 2019) - Wen, Zi‐Hao; Li, Lin; Li, Sheng‐Rong; Santosh, M.; Alam, Masroor; Yuan, Mao‐Wen; Li, Shi‐Sheng; Zhi, Ze‐Ya; Liu, Jia‐Wei
Abstract : The large‐scale concentration of Au associated with Mesozoic granitoid intrusions in the North China Craton (NCC) has inspired many investigations to explore the genetic relationship between the magmatism and gold metallogeny. The Xiaoqinling gold province is located in the southern margin of the North China Craton. The Wenyu and Huashan monzonitic granites formed at Early Cretaceous represent two of the important intrusions in this region, and a large number of gold deposits occur around the Wenyu pluton. Here we present results from an integrated study using in situ zircon U–Pb ages, trace elements, and Hf isotope to infer the composition and environmental changes during different evolution stages of the fertile Wenyu pluton and compare with the infertile Huashan pluton. The Huashan pluton was emplaced at 144.0 ± 0.6 Ma, whereas the fertile Wenyu pluton experienced multistage magmatic activity from 141.4 ± 0.6 to 129.6 ± 0.5 Ma. Temperatures computed from Ti‐in‐zircon thermometry indicate that the late‐stage Wenyu magma crystalized at 644°C, the Huashan magma, and early‐stage Wenyu magma crystalized at around 750°C. And the oxygen fugacity (Ce 4+ /Ce 3+ > 200 and Eu/Eu* > 0.7) and the water content of the late‐stage Wenyu magma stay at higher levels. The U/Yb–Hf and U/Yb–Y relationship with εHf(t) (−15.63 to −17.89) of the late‐stage Wenyu magma suggest that the ancient lower crust with subsequent inputted basaltic components make up the source of the fertile and infertile plutons. Combined with previous geochronological data and geodynamics studies, we propose that the late‐stage intrusion of the Wenyu pluton experienced intensive magma mixing. And the formation of Wenyu pluton created conducive heat energy, oxygen fugacity, and water conditions for the formation of high‐grade gold deposits.